On a persisting curious double standard in behavior analysis: Behavioral scholars' perspectives on procedural fidelity. Issue 2 (1st February 2023) - St. Peter, Claire C.; Brand, Denys; Jones, Stephanie H.; Wolgemuth, Jennifer R.; Lipien, Lodi
Abstract: Procedural fidelity is the extent to which independent variables are implemented as designed. Despite 40 years of discussion about the importance of procedural fidelity for behavioral research, reporting of fidelity data remains an uncommon practice in behavior‐analytic journals. Researchers have speculated about reasons for underreporting, but the perspectives of scholars about when reporting is warranted or necessary have not yet been explored. Thus, the purpose of this study was to evaluate possible reasons for infrequent reporting of fidelity data in behavior‐analytic studies. To address this purpose, we conducted focus groups with scholars in applied behavior analysis. Five themes emerged regarding why procedural fidelity data are not typically reported. We provide a discussion about how these themes are interrelated and offer suggestions and recommendations to assist with the collection and reporting of fidelity data.